Community associations of birds with amphibians and fish in wetlands created for biodiversity. (June 2023) - Kačergytė, Ineta; Knape, Jonas; Żmihorski, Michał; Arlt, Debora; Pärt, Tomas
Abstract: Conservation initiatives to support declining water-related biodiversity through wetland creation have increased during the last decades. Multiple studies have evaluated the suitability of created wetlands for birds and amphibians, but only a few have considered the species associations that might also affect the outcome. Using joint species distribution models, we explored species associations of birds, amphibians and fish in 52 created biodiversity wetlands in Sweden. As most of these wetlands were primarily created for increasing bird diversity, we asked whether the occurrence of fish and amphibians relates to bird species richness, pair abundance and chick abundance (as a measure of reproductive success) and whether conservation conflicts or synergies between birds, amphibians and fish can be observed. In general, we found positive bird-amphibian association patterns and negative bird-fish association patterns, although the uncertainties were high for these estimates. In line with previous research, the generally negative bird-fish co-variance indicates potential conservation conflicts between wetland creation for birds and fish, where fish might be introduced for recreational fishing or other ecosystem services. Therefore, our results suggest that it can be hard to benefit bird and fish communities with the same wetland, and separate wetland creation with different goals may be needed. The generally positive bird-amphibian species-species associations and the lack of previous studies revealing conflicts indicate synergies between wetland creation for birds and amphibians. However, research needs to further consolidate such synergies, including amphibian reproductive output from bird-rich wetlands. Graphical abstract: Unlabelled Image Highlights: We identify biodiversity conservation conflicts/synergies in created wetlands. We analyse bird-amphibian-fish associations using Joint Species Distribution Models. Positive bird-amphibian association patterns suggest synergy in wetland creation. Negative covariance between birds and fish species indicates conservation conflicts. Wetland co-creation feasible for birds with amphibians but not for birds and fish.